2013
DOI: 10.1038/bjc.2013.415
|View full text |Cite
|
Sign up to set email alerts
|

Stromal disrupting effects of nab-paclitaxel in pancreatic cancer

Abstract: Background:Nab-paclitaxel and gemcitabine have demonstrated a survival benefit over gemcitabine alone in advanced pancreatic cancer (PDA). This study aimed to investigate the clinical, biological, and imaging effects of the regimen in patients with operable PDA.Methods:Patients with operable PDA received two cycles of nab-paclitaxel and gemcitabine before surgical resection. FDG-PET and CA19.9 tumour marker levels were used to measure clinical activity. Effects on tumour stroma were determined by endoscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
179
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(194 citation statements)
references
References 19 publications
8
179
0
1
Order By: Relevance
“…Enzymatic and small molecule targeting of the periductal stroma has shown promise in remodeling the architecture, softening the tumor, decreasing interstitial pressure, and improving the efficiency of systemic delivery in pancreatic ductal adenocarcinoma. 59,60 As last, disease markers that forecast which patients are most likely to experience accelerated progression or recurrence based on intrinsic tumor biology are critically needed to inform patient expectations, guide patient surveillance measures, and tailor personalized treatment regimens. There is emerging interest to stratify patients on the basis on stromal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic and small molecule targeting of the periductal stroma has shown promise in remodeling the architecture, softening the tumor, decreasing interstitial pressure, and improving the efficiency of systemic delivery in pancreatic ductal adenocarcinoma. 59,60 As last, disease markers that forecast which patients are most likely to experience accelerated progression or recurrence based on intrinsic tumor biology are critically needed to inform patient expectations, guide patient surveillance measures, and tailor personalized treatment regimens. There is emerging interest to stratify patients on the basis on stromal characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…PDAC tumor stroma serves as a mechanical barrier and promotes tumor forma-tion, progression, invasion, and metastasis development. [32][33][34] Treatment with nab-paclitaxel alone or nab-paclitaxel in combination with gemcitabine has been shown to decrease cancer-associated fibroblast (CAF) content, inducing a marked alteration in cancer stroma that result in tumor softening both preclinically 29 and clinically 28 . In our studies, we also found that the G C nP doublet significantly reduced the number of a-SMA positive fibroblasts as well as reduced extracellular collagen.…”
Section: Discussionmentioning
confidence: 99%
“…Nab-paclitaxel has been shown to affect the tumor stoma. 28,29 In the present study, we evaluated the efficacy and safety profile of TH-302 in combination with gemcitabine and nab-paclitaxel in PDAC preclinical models.…”
Section: Introductionmentioning
confidence: 99%
“…Это отчасти связано с тем, что nab-паклитаксел в отличие от паклитаксела вызывает истощение обильной десмопластической стромы опухо-ли, характерной для РПЖ и участвующей в прогрессии опухоли и химиорезистентности. В итоге концентрация гемцитабина в опухолевой ткани увеличивалась почти в 3 раза [31][32][33].…”
Section: Nab-паклитаксел + гемцитабинunclassified